Burden and pattern of acute diarrhea in Thai children under 5 years of age: a 5-year descriptive analysis based on Thailand National Health Coverage (NHC) data - Busara Charoenwat; Kunanya Suwannaying; Watuhatai Paibool; Napat Laoaroon; Sumitr Sutra; Kaewjai Thepsuthammarat (BMC, 2022)
Abstract Background The incidence of acute diarrhea in Thai children under five years of age has increased over the last three decades. Even though mortality has significantly declined, the burden and cost of medical treatment are still high. Our objectives are to describe the burden and pattern of acute diarrhea cases that required admissions by Thai children under five years of age from 2015 to 2019. Methods Data regarding the admission of acute diarrhea cases of Thai children with Thailand National Health Coverage (NHC) under five years of age from 2015 to 2019, recorded as International Statistical Classification of Diseases and Related Health Problems, tenth Revision, Thai Modification (ICD-10-TM), were analyzed. Results The incidence trend of yearly acute diarrhea in children 0-5 years of age slightly increased from 33.36 cases per 1,000 population in 2010 to an average of 33.79 cases per 1,000 population/ year from 2015 to 2019 or approximately 0.43 cases per 1,000 population over the last decade while diarrhea-related mortality had a low, constant rate of 0.71 to 1.16 per 100,000 population per year. Two thirds of the mortality rate was observed in children under 1 year of age or 4.1 cases per 100,000 person-years in 5-year period (P < 0.01). The high cost of performing the medical treatment of approximately four hundred million baht per year. Seasonal variations demonstrated consistency with similar patterns during the cold and rainy seasons throughout the 5-year period. Regional distribution of the causative agent was also observed in Cholera, Typhoid, and Amoebiasis cases. A08: viral and other specified intestinal infections and A09: other gastroenteritis and colitis of infectious and unspecified origin were the two most common causes of diarrheal diseases. Conclusions The incidence rate of acute diarrhea in Thai children under five years of age was higher while the mortality rate of acute diarrhea was lower than those in the past decade. A similar seasonal outbreak of acute diarrhea was seen during each examined year. The causative agent was not significant and was mainly unspecific. Trial registration Number TCTR20220117002, date of registration: 17/01/2022, site: Thai Clinical Trials Registry, URL http://www.thaiclinicaltrials.org/show/TCTR20220117002